Pros and cons of fertirrigation with in natura sugarcane vinasse: Do improvements in soil fertility offset environmental and bioenergy losses? - Fuess, Lucas Tadeu; Altoé, Marcos Eduardo [UNESP]; Felipe, Mayara Caroline; Garcia, Marcelo Loureiro [UNESP] (Elsevier, 2021)
Managing vinasse in sugarcane biorefineries currently raises a direct debate between traditional industrialists of the sucro-energy sector and researchers. While the first group identifies fertirrigation (land disposal of in natura vinasse) as a well-consolidated approach, the latter understands vinasse as a potential substrate for numerous (bio)technological applications, in addition to associating environmental issues with fertirrigation. This study offers an unbiased assessment of fertirrigation using in natura vinasse by quantifying and qualifying its pros and cons. A comparative analysis using anaerobic digestion (AD) as an alternative management approach was carried out, presenting aspects of organic matter-derived pollution and bioenergy recovery from biogas. Field data obtained in five sugarcane cultivation areas subjected to fertirrigation within the period 2012–2016 revealed the adequate buildup of macronutrients (K+, Ca2+ and Mg2+) associated with high base (51.97–81.38%) and low aluminum (0.22–2.26%) saturation levels without evidences of overfertilization and sodification. However, the inputs of biodegradable organic matter along with nutrients trigger important environmental drawbacks, with emphasis on uncontrolled methane emissions (up to 732.10 kg–CO2–eq ha−1) and polluting potential levels equivalent to that of population densities as high as 293 inhab ha−1. Energy losses in all cultivation areas assessed could provide electricity to process at least 80% of the daily milling capacity of the reference biorefinery. Hence, gains in soil fertility do not offset the losses in environmental quality when land disposing in natura vinasse, and AD seems to be the primary approach to mitigate polluting issues and enhance resource recovery in sugarcane biorefineries.
Keywords: Biodigestion; Bioenergy recovery; GHG emissions; Soil fertility; Sugarcane biorefinery; Vinasse management